The association between oxidative stress and bone mineral density according to menopausal status of Korean women - Lee, Young Joo (Obstet Gynecol Sci, 2015)
OBJECTIVE: The aim of this study is to investigate the association between oxidative stress and bone mineral density (BMD) according to menopausal status of Korean women. METHODS: A total of 2,232 women who visited to the health promotion center at Pusan National University Hospital between 2010 and 2014 were included in this cross-sectional study. Laboratory tests, such as uric acid, albumin, total bilirubin, which were evaluated as a natural antioxidants. Homocysteine also was evaluated as a factor associated with oxidative stress. Correlation analyses and partial correlation coefficient between BMD scores and laboratory parameters associated with oxidative stress according to menopausal status were performed with Pearson test. RESULTS: By correlation analysis, uric acid had only positive correlation with femur and lumbar BMD in premenopausal and postmenopausal group. But albumin and bilirubin, which were the other natural antioxidants, had no correlation with BMD except total bilirubin with femur BMD in postmenopausal group. Homocysteine had negative correlation with femur BMD in postmenopausal group. But there were different results in partial correlation coefficient adjusted by age and BMI. In premenopausal group, uric acid was still positive correlation with femur and lumbar BMD, whereas in postmenopausal group homocysteine had no correlation with femur BMD, total bilirubin and uric acid had no correlation with lumbar BMD. At the multiple logistic regressions, only age and menopause status, uric acid had correlation with BMD. CONCLUSION: In this study, homocysteine had no correlation with BMD. But in natural antioxidant, uric acid had only positive correlation with BMD.